Jesuit Education and the Irish Catholic Elite - Ciaran O'Neill (Espacio, Tiempo y Educación, 2019)
Since their re-establishment in the early decades of the nineteenth century the Jesuits have successfully maintained a position at the pinnacle of Catholic elite education. In this article I propose to discuss Irish education in the context of global trends in cosmopolitan and elite forms of education. All across Europe we find the Jesuits competing for regional elites and sub elites in this period, and the Irish Jesuits are part of this transnational pattern. I will then focus on the two most important nineteenth century foundations –Tullabeg (1818-86) and Clongowes (1814-)– as the exemplary «elite» Jesuit boarding schools in Ireland. I will then briefly discuss two less socially ascendant but nevertheless important day schools, Belvedere College (1841-) and Gonzaga (1899-), both in Dublin. The educational product was intentionally politically muted, informed by a desire for Catholic advancement in all aspects of life, including imperial service, religious leadership, gaining a foothold in the prestigious professions, and –where possible– advocating for general Catholic advancement. As with Jesuit education elsewhere in this period it was an explicitly elitist project at the beginning of the nineteenth century, with greater market segmentation evident later in the century with the advent of the prestigious urban day-schools.